3w-40-2w+60+w=

Simple and best practice solution for 3w-40-2w+60+w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3w-40-2w+60+w= equation:


Simplifying
3w + -40 + -2w + 60 + w = 0

Reorder the terms:
-40 + 60 + 3w + -2w + w = 0

Combine like terms: -40 + 60 = 20
20 + 3w + -2w + w = 0

Combine like terms: 3w + -2w = 1w
20 + 1w + w = 0

Combine like terms: 1w + w = 2w
20 + 2w = 0

Solving
20 + 2w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + 2w = 0 + -20

Combine like terms: 20 + -20 = 0
0 + 2w = 0 + -20
2w = 0 + -20

Combine like terms: 0 + -20 = -20
2w = -20

Divide each side by '2'.
w = -10

Simplifying
w = -10

See similar equations:

| 13x+12=38 | | 4n-6=14 | | 15-12x=51 | | f(x)=10-4x | | 4x+18=x+33 | | -31/3b+b | | 8+6a=-28+24 | | 2(3.5x+6)=2.5x-2 | | 2=9x | | 1/2x+4=-3 | | 0.6x=-7.2 | | x^2+y^2-9= | | (x-3)(3x+5)=0 | | 3/4-1/2b=3b | | 7x+5=13x+5 | | -8z-7=3z-7+5z | | x^2+3x-6=7x+6 | | -18-6=(1+3x) | | 23x-29y=7 | | 5x^2(6x+2)= | | 4x^2+4xy^2+y^4= | | 200=(50-2x)(20-2x) | | 6xz-5x= | | 2(a+12)=4 | | 2(x+4)=4+2x | | 18/12=m/42 | | 6d+5d=-11 | | 3x+2-4(8-7)=90 | | 10+x-1/3x+0 | | 35=-5+2g-7g | | b+27.51=36 | | -8n-3=-11 |

Equations solver categories